2020
DOI: 10.1007/s10826-020-01705-5
|View full text |Cite
|
Sign up to set email alerts
|

Mothers’ Experiences of Having an Adolescent Child with Depression: An Interpretative Phenomenological Analysis

Abstract: Objectives Adolescence represents a significant period of vulnerability for the development of depression. Whilst research has begun to explore factors associated with the development, maintenance and outcomes of adolescent depression, there is little research investigating this experience from a parental viewpoint. The aim of this study was to explore mothers' experiences of having an adolescent child with depression. Methods Eight mothers of depressed adolescents were recruited following their child's clinic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
27
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(31 citation statements)
references
References 47 publications
1
27
0
Order By: Relevance
“…Consistent with this, many parents in the present study noted that the adolescent returned to their 'old self' once depressive symptoms receded. These findings are in line with Armitage et al (2020), who reported that parents of depressed adolescents witnessed their children behaving in more familiar ways as they began to recover. Pre-therapy interviews exploring IMPACT participants' expectations for therapy showed that while some adolescents hoped to rediscover their old self through therapy, others saw it as a chance to develop the self and acquire new capacities (Midgley et al, 2016).…”
Section: Discussionsupporting
confidence: 90%
“…Consistent with this, many parents in the present study noted that the adolescent returned to their 'old self' once depressive symptoms receded. These findings are in line with Armitage et al (2020), who reported that parents of depressed adolescents witnessed their children behaving in more familiar ways as they began to recover. Pre-therapy interviews exploring IMPACT participants' expectations for therapy showed that while some adolescents hoped to rediscover their old self through therapy, others saw it as a chance to develop the self and acquire new capacities (Midgley et al, 2016).…”
Section: Discussionsupporting
confidence: 90%
“…The current findings support previous studies that found an increased emotional burden associated with raising a child with autism, including increased levels of parenting stress, worry, and guilt among mothers, as well as feelings of being overwhelmed [ 56 , 57 ]. The mothers’ observations regarding the emotional impact of the child’s diagnosis concur with wider evidence from qualitative studies of parents of children with a range of developmental and mental health disorders who commonly expressed a desire not only to explain the individual experience, but further to search for the answer to an existential question, namely “why did this happen to us?” [ 58 ]. The idea that mothers are readily distressed echoes previous qualitative work, which indicated that parents of children with ASD experience distress and emotional turmoil [ 59 ] in relation to their child’s potentially dangerous and unpredictable behavior and functional dependency.…”
Section: Discussionmentioning
confidence: 99%
“…cheating, and temper tantrums) [ 29 ]. Also, a recently published study explored mothers' experiences of having an adolescent child with depression and revealed five interlinked superordinate themes, and the key finding across the themes was the emotional distress and sense of uncertainty experienced by the mothers [ 30 ]. Similarly, a recent study assessed longitudinal pathways between maternal depressive symptoms, parenting self-esteem, and infant temperament and found the mothers' confidence is influenced by their experience with a difficult infant and by their depressive symptoms [ 31 ].…”
Section: Discussionmentioning
confidence: 99%